TRADITIONAL PHILOSOPHY TRI HITA KARANA-ORIENTED EDUCATION IN SUPPORTING SUSTAINABILITY EDUCATION - Sholicha, Yuni Maratus; Supriatna, Nana; Wiyanarti, Erlina (Proceeding of International Conference on Islamic Education (ICIED); Vol 7 No 1 (2022): Proceeding of International Conference on Islamic Education (ICIED), 2022)
Nowadays Indonesia is one of the countries that is perfecting the delivery of the Sustainable Development Goals mission (SDGs) which is a follow-up idea from the Millennium Development Goals (MDGs) by the United Nations. The environmental problems that happen are not only caused by natural disasters but also caused by people's activities. in line with that, education should take a role in increasing the environmental awareness of the young generation as a changemaker.  To address this issue, it is highly possible to adopt the traditional ideology "Tri Hita Karana” to raise a generation of environmental stewards to reach positive results in attitude toward environmental sustainability. Tri Hita Karana, a traditional philosophy, is used in Green School Bali to instill ecological intelligence in children, raising their knowledge of environmental challenges. Tri Hita Karana, which strengthens students', teachers', and parents' understanding of the need to create a greener planet, is one of the core values at Green School Bali. In order to understand the essence of Tri Hita Karana as the Balinese ideology that is also utilized in the education of international students at Green School Bali, this qualitative research uses phenomenological type and descriptive analysis. To conclude, Tri Hita Karana as the ideology for Balinese that is applied in education for global students in Green School Bali instills a student's ecological intelligence that supports sustainable education. Moreover, Green School Bali has the global design to implement the values through social sciences subjects for their students from all over the world and successfully increase students’ green behavior with various challenges due to the diversity of students’ nationalities. Green School Bali is successfully develop students' ecological intelligence through applying green behavior related to Tri Hita Karana